Realtime IoT based Harmonics Monitoring System Review with Potential Low-Cost Devices with Experimental Case Study - Purnomo Purnomo; Aripriharta Aripriharta; Anik Nur Handayani; Rini Nur Hasanah; Norzanah Rosmin; Gwo-Jiun Horng (Universitas Ahmad Dahlan, 2021)
This paper presents a harmonic analyzer that used IoT and smart apps for low-cost and portable solutions. We contribute a short review of harmonics measurement methods and experimental approaches for monitoring harmonics using an IoT-based system. The proposed device was built from a current sensor, a voltage sensor, and a microcontroller with an IoT transmitter which is integrated with MatlabÂ© cloud and smart apps (android). In specific, we experimented with testing and validated our proposal using the standard instrument under a fair treatment. The measurement scenario was taken on the point of comment coupling in the building campus for 5 to 10 minutes of each comparable instrument. Based on experimental results, the proposed device could monitor the harmonics profile drawn by the loads in the building campus. The trade-off between cost and performance is founded as the truth that it takes about 1 minute to update the harmonics data. Furthermore, the average error of THDV is 5.7%, and THDI is 4.7% which is higher than the expensive instrument. These values are acceptable based on IEEE standards.Â Besides, it could monitor harmonics in real-time through an android application which is easy to use and portable. In addition, the cost of making the proposed device is cheap compared to the price of the standard instruments in the market.